STUDY OF CRITICAL FACTORS OF SOCIAL TENSION IN REGIONAL SYSTEMS - Nataliia Gavkalova; Nataliia Stepanenko; Oleksandr Ponomarenko (Baltic Journal of Economic Studies, 2023)
Purpose. The purpose of the study is to identify and study critical factors of social tension in different economic regions of Ukraine using a modern set of models for analysis and assessment of the level of social tension in conditions of transformation of the structure of modern society for timely prevention and avoidance of social disparities and uneven development. The main stages of measuring the level of social tension are highlighted: analysis and determination of a set of parameters for assessing social tension, their classification according to their impact on society, formation of a set of initial data, calculation of group integral indicators, construction of a general integral indicator of social tension. The main stages of the study of regions by the level of social tension are defined: a graphic representation of the levels of tension in the regions, the study of the dynamics of the formation of the levels of social tension, the establishment of the main factors of its formation in the regional dimension, the classification of objects by the level of social tension. Value/originality. Theoretical analysis of the content and role of social tension in the economic system was conducted, the main indicators and criteria of social tension were considered, a set of models for analysis and evaluation of social tension in various economic regions of the world and in Ukraine in particular was proposed and implemented. The thesis proposes a conceptual research model divided into two main modules: Module 1 – Assessment and analysis of social tensions; Module 2 – Building a regional development programme. Within the first module, assumptions about the criteria and indicators of social tensions are made, the boundaries of the system are determined, the external environment is described, its essential elements are highlighted and described. The selection of the criteria of social tension was carried out according to the following groups of factors: economic, demographic, political and social, the demarcation of substitutes and those that were included in the model and those that were not analysed by the researcher was carried out. Results. Multiple regression models have been constructed and the most significant variables that have the strongest influence on the resulting criterion have been selected. The second module defines the directions of development of the regions, based on all the data and models obtained previously. The main factors that are indicators of social tensions are identified, namely: the number of people with at least a school education; gross domestic product; total population; average length of study. Practical implications. With the help of economic and mathematical tools, the most important indicators of social tension were formed and determined for each region of Ukraine and the country as a whole, among which the level of income and education are the most critical. The results of the study can be put into practice to normalise the social balance in the country, to overcome the disparities in the development of different segments of the population.